Quality of life in adults with ADHD after neuropsychiatric coaching - Kallio, Petri (My University, 2025)
The prevalence of ADHD has increased in the last years and is currently 4,4% worldwide. Individuals with ADHD have statically significantly lower quality of life than neurotypical individuals. This is mainly because of the difficulties in regulating activity, attention and impulsivity. Coaching is an intervention that is goal-oriented and collaborative method. Coaching aims to support the individual in making a behavioral change to reduce the symptoms of ADHD. The purpose of this study was to describe the quality of life in adults with ADHD after neuropsychiatric coaching. The goal of this study was to recognize the impact of neuropsychiatric coaching to quality of life among adults with ADHD and to determine the elements of neuropsychiatric coaching that leads to positive outcomes for the individual in the coaching process This study was conducted with integrative literature review. The search was conducted 24.2.2025 from Pubmed, Cinahl, PsycInfo, Scopus and Medic. Articles identified from the databases was overall n=816. Studies included in this review was n=14. The quality appraisal of studies was done with JBI quality appraisal tool. The selected articles were analyzed with inductive content analysis. This study suggests that coaching had positive effect on several dimension of quality of life. These positive effects were also long-term. This study also identified several elements in coaching process that led to positive outcomes for the individual. These elements were categorized in internal elements and external elements of coaching.
Keywords: ADHD, Attention deficit hyperactivity disorder, Quality of Life, Neuropsychiatric coaching, ADHD Coaching, Coaching